CONCEPTUAL MODEL OF INTERNALIZATION OF RELIGIOUS ETHICAL VALUE IN EDUCATION PERSPECTIVE ISLAMIC CHARACTERS - Nadri Taja; Encep Syarief Nurdin; Aceng Kosasih; Edi Suresman (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
This study aims to find the concept of religious ethical values in the perspective of Islamic character education. The research method used is library research (literature study) in which the researcher conducts a review of the theories that come from books or journals that are relevant to the topic under study. The result of this research is a conceptual model of internalization of religious ethical values which is built on three concepts, namely first, tafhim (understanding) aims to know about knowledge; second, tazkiyatun nafs (purifying the soul) aims to want to improve itself through the process of takhalli (cleansing the soul) from sin and tahalli (beautifying oneself) with pious deeds; third, tahdzib (nurturing the soul) aims to be able to do good through mujahada, namely consistent sincerity in truth and riyadhah, namely training oneself to be always busy doing good deeds and leaving bad deeds. Thus, educational activities do not only focus on the transfer of knowledge, but also the transfer of value. Because education is not just about teaching reason alone. But more than that, education must be able to form a good character. AbstrakPenelitian ini bertujuan untuk menemukan konsep nilai etis religius dalam perspektif pendidikan karakter islami. Metode penelitian yang digunakan bersifat library research (studi kepustakaan) yang mana peneliti melakukan penelaahan terhadap teori-teori yang bersumber dari buku-buku atau jurnal yang relevan dengan topik yang diteliti. Hasil penelitian ini adalah konseptual model internaliasasi nilai etis religius yang dibangun pada tiga konsep, yakni pertama, tafhim (memahami) bertujuan untuk tahu tentang pengetahuan; kedua, tazkiyatun nafs (menyucikan jiwa) bertujuan untuk mau memperbaiki diri melalui proses takhalli (membersihkan jiwa) dari perbuatan dosa dan tahalli (memperindah diri) dengan amal soleh; ketiga, tahdzib (memelihara jiwa) bertujuan untuk mampu berbuat kebaikan melalui mujahadah yakni kesungguhan konsisten dalam kebenaran dan riyadhah yakni melatih diri senantiasa sibuk melakukan perbuatan baik dan mengginggalkan perbuatan buruk. Dengan demikian, kegiatan pendidikan tidak hanya fokus pada transfer of knowledge saja, melainkan juga transfer of value. Karena pendidikan bukan sekadar membelajarkan akal semata. Akan tetapi lebih dari itu, pendidikan harus mampu membentuk karakter yang baik (good character).